2021
DOI: 10.1111/codi.15969
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged postoperative ileus following right‐ versus left‐sided colectomy: A systematic review and meta‐analysis

Abstract: Aim: Prolonged postoperative ileus (PPOI) is a common complication following colonic surgery, and is associated with longer hospital stay, greater risk of complications and substantial cost for patients and hospitals. Some reports have recently suggested that gastrointestinal (GI) recovery varies based on the side of resection (i.e., right-sided vs. left-sided colectomy). This systematic review and meta-analysis aimed to compare GI recovery by resection side. Methods:The MEDLINE, Embase, Cochrane Library and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
12
1
Order By: Relevance
“…ERH led to increased postoperative Hb drop in this series, which has also been demonstrated to be an independent risk factor for PPOI 17 . Reported rates of ileus following right‐sided colonic resections are variable (15–36%), 6,11,15,17,20 with considerable heterogeneity in defining PPOI 1,9 . The rates of PPOI in this study (80/293, 27% over the whole sample) are higher than most reported in the literature, although local studies have reported similarly high rates of PPOI, including at 36% in a cohort where the same rigorous definition for PPOI was utilized and open/laparoscopic techniques were more equally represented than in our sample 15,17 …”
Section: Discussionmentioning
confidence: 38%
See 3 more Smart Citations
“…ERH led to increased postoperative Hb drop in this series, which has also been demonstrated to be an independent risk factor for PPOI 17 . Reported rates of ileus following right‐sided colonic resections are variable (15–36%), 6,11,15,17,20 with considerable heterogeneity in defining PPOI 1,9 . The rates of PPOI in this study (80/293, 27% over the whole sample) are higher than most reported in the literature, although local studies have reported similarly high rates of PPOI, including at 36% in a cohort where the same rigorous definition for PPOI was utilized and open/laparoscopic techniques were more equally represented than in our sample 15,17 …”
Section: Discussionmentioning
confidence: 38%
“…Recent systematic review discusses a number of possible underlying mechanisms why PPOI is more common following right (vs. left)‐sided colorectal resections 9 . Rectosigmoid motor hyperactivity following right sided resections, demonstrated by high‐resolution manometry, has been suggested as a contributor towards PPOI 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 Previous reports have shown a difference in the occurrence of POI after colorectal cancer surgery between the left and right sides, with the right-side colon being at higher risk than the left-side colon. 4,5 Factors reported to contribute to POI include clinical features, epidemiological features, histological characteristics, and molecular biological differences between sides. [6][7][8] However, past reports have included various biases such as single-center reports, small study cohorts, and perioperative management differing from that in recent years.…”
Section: Introductionmentioning
confidence: 99%